Reproduction and biochemical responses in Enchytraeus albidus (Oligochaeta) to zinc or cadmium exposures - Novais, Sara C.
To better understand chemical modes of action, emphasis has been given to stress responses at lower levels of biological organization. Cholinesterases and antioxidant defenses are among the most used biomarkers due to their crucial role in the neurocholinergic transmission and in cell homeostasis preventing DNA damage, enzymatic inactivation and lipid peroxidation. The main goal of this study was to investigate the effects of zinc and cadmium on survival and reproduction of E. albidus and to assess metals oxidative stress potential and neurotoxic effects at concentrations that affected reproduction. Both metals affected the enchytraeids' survival and reproduction and induced significant changes in the antioxidant defenses as well as increased lipid peroxidation, indicating oxidative damage. This study demonstrates that determining effects at different levels of biological organization can give better information on the physiological responses of enchytraeids in metal contamination events and further unravel the mechanistic processes dealing with metal stress. (C) 2011 Elsevier Ltd. All rights reserved.